Techno-Science, Integral Thought, and the Reality of Limits in Laudato Si’ - Sideris, Lisa (The Trumpeter, 2018)
"Reality" is a term that appears dozens of times in Pope Francis’s Laudato Si’. The term is not directly defined, but appears to signal for Francis a mysterious, relational, created order that imposes limits on humans while also evoking positive feelings like wonder and peace. Francis contrasts this vision of reality with perspectives on the world that are human-centered, fragmented, or reductionist. In this way, his account of reality grounds his sharp critique of narrow, techno-scientific perspectives on life and the world that entail a will to mastery and control. Francis’s critique of reductive, fragmentary perspectives is also connected to his concern with a category of humans and nonhuman others whom Francis designates “the excluded” in Laudato Si’. Distorted views of reality perpetuate neglect of these excluded others and prevent us from grasping the integral functioning of human, ecological, and social realms. I conclude by contrasting Francis’s version of integral ecology with other forms of integral thought that express naïve enthusiasm for technology, and suggest a denial of human and natural limits.